2019
DOI: 10.1002/adts.201900126
|View full text |Cite
|
Sign up to set email alerts
|

Titanium(IV) Inclusion as a Versatile Route to Photoactivity in Metal–Organic Frameworks

Abstract: Titanium-containing metal-organic frameworks (MOFs) are known to perform light-promoted chemical transformations. Formation of these frameworks, accessed either natively or via transmetallation, can instill beneficial photocatalytic properties in previously photo-inert scaffolds. Band edge diagrams coupled with their density of states illustrate the persistent nature of the accessible titanium d-states at the conduction band edge, independent of linker identity. In essentially all of these Ti-containing framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 65 publications
3
20
0
Order By: Relevance
“…The postsynthetic exchange of metal ions in the node can introduce new bands, typically vacant ones, into a desirable energy range. In principle, the band gap can then be controlled by low‐lying, vacant orbitals of the dopant, such as 3d orbitals of Ti [39, 40] …”
Section: Band Alignmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The postsynthetic exchange of metal ions in the node can introduce new bands, typically vacant ones, into a desirable energy range. In principle, the band gap can then be controlled by low‐lying, vacant orbitals of the dopant, such as 3d orbitals of Ti [39, 40] …”
Section: Band Alignmentmentioning
confidence: 99%
“…Important work, certainly from the application perspective, involves the development of new Ti‐based MOFs that bring an improved stability in catalytic reactions. Predicted in computation by Mancuso and Hendon, there is some robustness to the Ti 3d band alignment with respect to linker identity [40] . One way to improve stability is to employ stronger metal–ligand bonds.…”
Section: Band Alignmentmentioning
confidence: 99%
“…20 Combining the best of both approaches, metalorganic frameworks (MOFs) merge the benefits of heterogeneous catalysis and synthetic modularity. [21][22][23][24] Previous studies in MOF catalysis have primarily focused on thermally driven reactions at either the linker or node using intrinsic [25][26][27] and extrinsic [28][29][30] catalytically active metals. Conversely, MOF photoredox chemistry [31][32][33] typically focuses on electron transfer between the inorganic and organic MOF components 34 , shuttling electrons to interstitial molecular catalysts [35][36][37] or guests [38][39][40][41] .…”
Section: Introductionmentioning
confidence: 99%
“…EPR later validated the mechanism of Ti III formation. 50 Paired with electronic structure calculations, Ti III -formation was rationalized by identifying the conduction band minimum (CBM) origin as vacant Ti d-states in the pristine MOF — a general property extending to all reported Ti IV -containing MOFs, 25 and likely a general consideration when designing photoactive MOFs with inorganic-centered conduction bands.…”
Section: Introductionmentioning
confidence: 99%
“…Changing Bands with Metal Substitution Thepostsynthetic exchange of metal ions in the node can introduce new bands,t ypically vacant ones,i nto ad esirable energy range.I np rinciple,t he band gap can then be controlled by low-lying,v acant orbitals of the dopant, such as 3d orbitals of Ti. [39,40] Thef irst case that employed such postsynthetic metal exchange for photocatalytic application came by Sun et al,w ho exchanged Zr 4+ for Ti 4+ in aminated UiO-66. [41] DFT calculations confirmed that states from Ti 4+ were indeed responsible for al owering of the gap.…”
Section: Postsynthetic Modification and Ligand Exchangementioning
confidence: 99%